SPE Russian Oil and Gas Exploration &Amp; Production Technical Conference and Exhibition 2014
DOI: 10.2118/171285-ru
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Solids Transport Studies and Applications in Oil and Gas Industry - Experimental Work (Russian)

Abstract: Обзор исследований транспорта твердых веществ и применение в нефтегазовой промышленности (Overview of Solids Transport Studies and Applications in Oil and Gas Industry) -Экспериментальная работаЛи, Дж. и Б. Лафт, «Трайкан Велл Сервис» Авторское право 2014 г., Общество инженеров нефтегазовой промышленности Этот доклад был подготовлен для презентации на Российской технической нефтегазовой конференции и выставке SPE по разведке и добыче, 14 -16 октября, 2014, Москва, Россия.Данный доклад был выбран для проведения… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, Rabia has considered the effect of annulus size on cuttings transport minor. Rabia (1989), Sifferman and Becker (1992), Campos (1995), Larsen et al (1997), Azar and Sanchez (1997), Duan et al (2006), Li et al (2004), Bilgesu et al (2007), Li and Luft (2014a), Cayeux et al (2014), Zhang (2015), Reda et al (2018), Huque et al, 2020a, 2022, Deshmukh and Dewangen (Deshmukh and Dewangan, 2022 and Abbas et al (2022) have studied the effect of cuttings size on hole cleaning. Rabia and, Sifferman and Becker have considered cuttings size influence on hole cleaning as moderate while Li and Luft have reported it minor for the cuttings sizes [0.15, 7] mm.…”
Section: Annulus Sizementioning
confidence: 99%
See 1 more Smart Citation
“…However, Rabia has considered the effect of annulus size on cuttings transport minor. Rabia (1989), Sifferman and Becker (1992), Campos (1995), Larsen et al (1997), Azar and Sanchez (1997), Duan et al (2006), Li et al (2004), Bilgesu et al (2007), Li and Luft (2014a), Cayeux et al (2014), Zhang (2015), Reda et al (2018), Huque et al, 2020a, 2022, Deshmukh and Dewangen (Deshmukh and Dewangan, 2022 and Abbas et al (2022) have studied the effect of cuttings size on hole cleaning. Rabia and, Sifferman and Becker have considered cuttings size influence on hole cleaning as moderate while Li and Luft have reported it minor for the cuttings sizes [0.15, 7] mm.…”
Section: Annulus Sizementioning
confidence: 99%
“…They have shown that the higher the cuttings density the poorer is the cuttings transport efficiency. Iyoho (1980), Tomren et al (1986), Okrajni and Azar (1986), Rabia (1989), Becker et al (1991), Campos (1995), Azar and Sanchez (1997), Li and Walker (1999), Adari et al (2000), Li et al (2004), Mitchel and Ravi (Mitchell, 2006), Li et al (2004), Bilgesu (Bilgesu et al, 2007), Ahmed et al (2010), Nazari et al (2010), Ogurinde and Dosunmu (Ogunrinde and Dosunmu, 2012), Li and Luft (2014a), Zhang (2015), Benjamin (Werner, 2018), Sayindla (2018), Reda et al (2018), Huque et al, 2020a, 2022, Deshmukh and Dewangen (Deshmukh and Dewangan, 2022) and, Rasool and Aadnøy (Rasool Khosravanian, 2022 have reported drilling fluid flow rate to be one of the major drilling parameters affecting cuttings transport during drilling. Azar and Sanchez have identified drilling fluid flow rate dominant over all other drilling parameters for cuttings transportation.…”
Section: Cuttings Size and Densitymentioning
confidence: 99%
“…A submarine fan is defined as a kind of fan-shaped or conical sedimentary body, which transports terrigenous debris to the seafloor through the submarine canyon in the front of the continental slope [10][11][12]. The submarine-fan sandstone reservoirs deposited in a deep water environment has strong heterogeneity owing to variable depositional textures and compositions among different lithofacies [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups focus on hole cleaning experiments. A thorough summary of their work including their experimental equipment has been developed by Li and Luft [10]. In the following, results from large scale laboratory tests using field applied fluids are used to compare the hole cleaning performance of oil and water-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%